Asian earthquake: report from the first volunteer British hospital team in Pakistan. Issue 8 (25th July 2007) - Laverick, S; Kazmi, S; Ahktar, S; Raja, J; Perera, S; Bokhari, A; Meraj, S; Ayub, K; da Silva, A; Pye, M; Anser, M; Pye, J
Abstract : At 8:52 am on 8 October 2005 a massive earthquake wracked northern Pakistan and Kashmir. Various teams were sent to Islamabad and the disaster region from the UK. We discuss the types of injury patterns seen and recommend that a central register of volunteers should be created to deal with similar situations in the future.